SOSIALISASI SWAMEDIKASI BERBASIS TANAMAN OBAT KELUARGA PADA MASYARAKAT RW.04 KELURAHAN MERUYA UTARA, JAKARTA BARAT - Harizal Harizal; Muchammad Reza Ghozaly; Inherni Marti Abna; Robby Rijal Sauri; Rizkia Nuraida; Ahmad Jakaria Karim; Fauzia Zahriatul Wildan; Iswatul Fauzizah; Sabna Allisya Firti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Self-medication is the treatment performed by patient for diseases that are self-recognized using medicines that are considered safe and effective without any diagnosis and prescription by professionals. Excessive practice of self-medication will have negative effects for the patient such as excessive drug abuse, delay in getting medical treatment, etc. This students’ community service aimed to socialize responsible self-medication practices to the community in RW.04, Meruya Utara, West Jakarta by using family medicinal plants. This series of activities were begun with counseling and training on the process of cultivating, harvesting, and post-harvest processing of family medicinal plants, and followed by counseling on self-medication by using family medicinal plants. Participants' understanding was evaluated by using a questionnaire filled out before and after the activities. The data obtained from the questionnaire showed that the participants have better understanding in practicing self-medication by using family medicinal plants with the understanding level of >70%.